Influence Model of Learning PBL and CTL on the Ability of Thingking Critical Student Learning Mathematical and Independence Junior High School - Faridatul Husna (JMEA : Journal of Mathematics Education and Application, 2022)
The problem studied in this research is the Effect of PBL and CTL Learning Models on Students' Mathematical Critical Thinking Ability and Independent Learning of Students. This study aims to determine: a (1) The significant effect between the PBL model and the CTL model on students' mathematical critical thinking skills, (2) The significant influence between the PBL model and the CTL modelon Student Learning Independence, (3) Interaction between early mathematics ability and learning model on students' mathematical critical thinking ability, (4) interaction between early mathematics ability and learning model on student learning independence . This research is a quasi-experimental research. The instruments used consisted of: (1) tests of students' initial mathematical abilities, (2) tests of students' mathematical critical thinking skills, (3) Student Learning Independent Questionnaires . The data in this study were analyzed using inferential analysis . Inferential data analysis was performed by analysis of covariance and ANACOVA. The results showed that: (1) There was a significant effect between the PBL model and the CTL model on the students' mathematical critical thinking skills, (2) There was a significant effect between the PBL model and the CTL model on independence. student learning, (3) There is no initial interaction of early mathematical ability with the model on students' mathematical critical thinking skills, (4) There is no initial interaction of early mathematical ability with the model on student learning independence.